Feeding horses in hot and humid conditions - Morgan, Karin (MTT, 2008)
The aim of this paper is to review feeding and management of the athletic horse in hot and humid conditions, which challenges the thermoregulatory system due to physical limitations of rate of heat loss. The following major recommendations for horse practice were concluded. The horse needs to acclimate three weeks to hot and humid conditions before maximal exercise can be performed. Adjust the workload to the actual climate conditions and if possible let the horse work during mornings and evenings. A suitable diet for high performing horses is a mix of hay/oats/vegetable oil (45/45/10) to get a lower heat production. The protein intake should be adequate with the right quality but kept as low as possible. Feed roughage during the cold part of the day to ease the heat load from fermentation. Extra water and electrolytes are lost due to increased sweat loss. Water is recommended to be offered ad lib from a bucket, which can increase the intake by 30%. Extra salt (NaCl) need to be added to the feed, but only supplement potassium after exercise in recovery. Keep the horse lean and clip it to facilitate heat loss and keep as much as possible out of bright sunlight.
Keywords: Ko; horse; heat; acclimation; nutrition; electrolytes